WAYS TO PRACTICE ORAL SPEAKING SKILLS - Hamdamova, Kamola Luqmonjon qizi (Innovative Development in Educational Activities, 2023)
Language encompasses a range of aspects that enable individuals to communicate through diverse means. Discover the attributes and significance of verbal language, as well as the most prevalent ones. Verbal language refers to a language spoken using the vocal cords and hand gestures, both of which are widely utilized. Numerous features constitute spoken language, such as phonology, morphology, syntax, and pragmatics. Each of these elements plays a crucial role in how spoken language is used and comprehended. The aim of this article is to provide the production of speech appearance in the study of English as a language, through learning. providing methodical recommendations on the production and practical application of methods for ensuring freedom of speech and performing this task; providing information about the modern methods, methods and training manuals used today, giving them free speech and making methodological recommendations on the production and implementation of methods for the implementation of this task